ADHD Behavior and Entrepreneurial Behavior: The Mediating Role of Entrepreneurial Intention - Tamzini , Khaled (Jordan Journal of Business Administration, 2024)
The fundamental objective of this research is to study the relationship between Attention-Deficit/Hyperactivity Disorder (ADHD) behavior and entrepreneurial behavior in Tunisian students. Based on the theory of person-environment adjustment (P-E), the theory of planned behavior (TPB) and the analysis of data collected from 267 Tunisian students using a self-administered online questionnaire, the results of the present study showed no relationship between ADHD behavior and entrepreneurial action. However, entrepreneurial intention plays a mediating role in this relationship. These results constitute a theoretical contribution to the entrepreneurial field. Similarly, the results of the current study lend further support to the person-environment “P-E” theory, which posits that the functionality of a component of ADHD behavior depends on its fit with the environment. In particular, the uncertain and autonomous entrepreneurial environment could be an attractive career choice for people who display hyperactive/impulsive behavior. As for the theory of planned behavior “TPB,” the results of this study also show that intention is a fundamental antecedent of entrepreneurial behavior. This research has practical implications. Its results can be used by stakeholders in the entrepreneurial ecosystem (teachers, incubators, career coaches,… etc.) to detect future entrepreneurs and absorb the unemployment of Tunisian university graduates.